The connectedness effect of dispersed materials on gas dedusting systems efficiency; IFOST 2012; Vol. 1 - Dodonova I. V. (Section 1. Chemical engineering and "Green technology", 2012)
The gas dust removal process in filters is achieved in the formed filtered particles layer, which thickens and becomes denser. In the gas filtering process through the porous diaphragm the precipitated dust is located in agglomerated state. Layer packing with particles accumulation is connected with the aggregates reformation. A layer porosity and particles calculated diameter are variable quantities. It is found that the hydraulic layer characteristics from the large particles have a linear form, from the small particles - nonlinear, and the dispersed medium compression during the filtration occurs throughout the entire layer. The rate of gas filtration with an acceptable pressure differential is determined by the particles connectedness.